WHO ARE WINE TOURISTS? AN EMPIRICAL INVESTIGATION OF SEGMENTS IN SERBIAN WINE TOURISM - Sekulić, Dejan; Petrović, Aleksandar; Dimitrijević, Vladimir (Economics of Agriculture, 2017)
This paper aims to investigate who are the wine tourists in Serbia. The research was conducted by using a survey method. Two profle questions were used aimed to identify segments: "Do you consume wine?" and "Have you ever visited some winery in Serbia"? Of a total number, 152 completed questionnaires were received. According to the research results, two segments of wine tourists were defned: active and potential. The active wine tourists are persons who consume wine and so far have visited some wineries and participated in wine tourism. The potential wine tourists also consume wine, but havent visited any winery in Serbia so far. Motives for inclusion in wine tourism of both these groups are similar, while the active wine tourists have shown greater readiness to revisit the favourite winery and participate actively in wine tourism in future period in regard to the potential ones.